The Syntactic Role of Arabic Language on Accusative Adjunct in The Book Nashā'iḥul-‘Ibād: An Overview to The Grammar Role and Reference - Khabib Akbar Maulana; Moh Masrukhi (Arabic Literature Department, 2021)
This research explains the categories and syntactic roles of Arabic in the book Nashâ? Iħul-ʕIbâd by Syekh Nawawi Al-Bantani based on the theory of roles and references grammar. This research is a descriptive qualitative with a purposive sampling method of presenting data that is separated from 112 data. The research method used in this study is the Agih method with basic techniques for direct elements using advanced techniques in the form of markup reading techniques on lingual element in Arabic grammar. The theory for determining the accusative adjunct markers of Arabic used is Valin's (1993) role and reference grammar theory using Kroeger's (2005) definition to look for core and peripheral elements in sentences. This research has found that the word categories of accusative adjunct can be the noun 'ism', the determiner 'muhaddad', the adjective 'naʕt', the adverb 'dharf', and the negation 'nafi', while the phrase category is the nominal phrase 'al-ʕibarah. al-ismiyyah ', the adverbial phrase 'al-ʕibarah adh-dharfiyyah ', and the adjective phrase' al-ʕibarah an-naʕʈiyyah '. In terms of the role of grammar syntax role and reference, adjunct can have any function as a clause modifier with evidential functions, as a core modifier with a function of manner, place, location, cause, and quantity, and also as a nucleus modifier with a affirmating function.